MINAT SISWI PUTRI DALAM MENGIKUTI PEMBELAJARAN PENDIDIKAN JASMANI KESEHATAN DAN REKREASI SAAT TERJADI MENSTRUASI DI SMAN 1 SUNGAI APIT - Pitrianti, Opta; Juita, Ardiah; Syahriadi, Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: Physical education, sports and health (Penjasorkes) have clear and directed pedagogic targets because movement as a physical activity is a natural basis for humans to learn to know the world and themselves which develops in accordance with the progress of the times and the prevailing educational orientation. In this way, it is clear that physical education has an important meaning in improving life skills in the maturation of students. Aims to develop aspects of physical fitness, movement skills, critical thinking skills, social skills, reasoning, emotional stability, moral actions, aspects of a healthy lifestyle, and introduction to a clean living environment. All of this is planned systematically in order to achieve national education goals. Dysmenorrhea is pain that occurs during menstruation. The pain that occurs is caused by several factors, from lack of physical movement and can also be triggered by stressed thoughts. This pain often appears before and during menstruation. In this situation, a person often feels uncomfortable and even unable to carry out activities because of the pain experienced during menstruation, so that this interferes with a person's activities and a person's motivation to do something. Many female students think that menstruation is an obstacle to sports activities. Because during menstruation it often causes pain, pain in the stomach, weakness, dizziness and discomfort. In this way, female students will indirectly experience limitations in movement. So that students' movement activities in playing sports are not free, which can cause a decrease in students' motivation and interest in participating in sports. Menstruation is an event experienced by women as a sign that someone is experiencing puberty. Menstruation is bleeding that occurs in women once every month during the fertile period except during pregnancy (Wianti & Pratiwi, 2018). Generally the menstrual cycle is 28 days with a duration of 4-7 days.Key Words: Education, Menstruation